Analisis Faktor-Faktor yang Mempengaruhi Pendapatan Usahatani Jagung Manis (Zea mays L. Saccharata) di Kelurahan Gunung Dempo Kecamatan Pagar Alam Selatan Kota Pagar Alam: Usahatani Jagung Manis - Munsiarum; Fikri Awaludin (Sekolah Tinggi Ilmu Pertanian (STIPER) Belitang, 2024)
The aim of this research is to calculate the amount of sweet corn farming income and analyze the effect of using production inputs such as land area, seeds, fertilizer and labor on sweet corn farming income in Gunung Dempo Village, Pagar Alam Selatan District, Pagar Alam City. This research was carried out in Gunung Dempo Village, Pagar Alam Selatan District, Pagar Alam City. The location selection was carried out purposively with the consideration that in Gunung Dempo Village there are several farmers who cultivate sweet corn. The research was carried out in February 2023. The research method used in this research is the survey method. The sampling method used in this research is the census method. In this study, the sample consisted of 25 respondents from 25 populations who farmed sweet corn in Gunung Dempo Village, Pagar Alam Selatan District, Pagar Alam City. The research results show that the average production cost of sweet corn farming in one planting season is IDR 5,980,200, revenue is IDR 12,400,000 and income is IDR 6,419,800. The R/C ratio value is 2.07. The use of sweet corn farming production factors has a real influence if tested together. All the variables tested (land area, seeds, fertilizer and labor) show a very significant influence on sweet corn farming production. However, if tested partially, then only the land area variable has a significant effect. The land area variable has a significant effect on the income of sweet corn farmers because the larger the land owned, the higher the farmer's income. The seed cost variable does not have a significant effect on sweet corn farming income. This means that the more seeds used, the greater the production results, but there is still a maximum usage limit. The fertilizer cost variable has no significant effect on sweet corn farming income because fertilizer use must be in accordance with the recommended dose. If it is exceeded, it can cause plant death and continuous application of fertilizer can have a bad impact on soil conditions. The labor cost variable does not have a significant effect on farmers' income because the more labor used, the lower the income needed to provide wages. The labor used in this case is daily workers.